2019
DOI: 10.3390/jcm8020257
|View full text |Cite
|
Sign up to set email alerts
|

Expression of SLC5A5 in Circulating Tumor Cells May Distinguish Follicular Thyroid Carcinomas from Adenomas: Implications for Blood-Based Preoperative Diagnosis

Abstract: Preoperative diagnosis of thyroid nodules reduces unnecessary surgery. Circulating tumor cells (CTCs) may contain information of primary tumor(s). We asked whether the peripheral blood expression of genes specific for circulating tumor cells (CTCs) differentiates benign thyroid nodules from malignant nodules. Peripheral blood mononuclear cells from thyroid nodule patients (n = 20) were isolated preoperatively and the expression of seven CTC-associated genes was measured in patients with thyroid nodule(s) (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…In the pre-operatory setting, the expression of genes associated with CTCs can help distinguish benign from malignant thyroid nodules with the follicular feature. For example, the expression of the CTC-associated gene SLC5A5 is lower in liquid biopsies of patients with FTC compared to patients with follicular adenoma (FA), while LGALS3 expression is higher in PTC than in FTC patients [ 34 ]. In the follow-up of surgically removed PTCs, serum levels of circulating epithelial cells (CECs) expressing epithelial cell adhesion molecule (EpCAM) and thyroid-stimulating hormone receptor (TSHR) are significantly higher in patients with disease recurrence and undetectable serum Tg due to TgAb [ 35 ].…”
Section: Liquid Biopsy In Differentiated Thyroid Cancermentioning
confidence: 99%
“…In the pre-operatory setting, the expression of genes associated with CTCs can help distinguish benign from malignant thyroid nodules with the follicular feature. For example, the expression of the CTC-associated gene SLC5A5 is lower in liquid biopsies of patients with FTC compared to patients with follicular adenoma (FA), while LGALS3 expression is higher in PTC than in FTC patients [ 34 ]. In the follow-up of surgically removed PTCs, serum levels of circulating epithelial cells (CECs) expressing epithelial cell adhesion molecule (EpCAM) and thyroid-stimulating hormone receptor (TSHR) are significantly higher in patients with disease recurrence and undetectable serum Tg due to TgAb [ 35 ].…”
Section: Liquid Biopsy In Differentiated Thyroid Cancermentioning
confidence: 99%
“…Although most PTC patients have a good prognosis, LNM often occurs in the early stage, and predicting and diagnosing LNM in advance can prevent patients from experiencing unnecessary pain. The discrimination of follicular lesions is another difficulty in TC, and the current traditional diagnostic methods are often inadequate (52,59). Samsonov et al compared patients with benign thyroid nodules, and found that miR-31 in the serum exosomes of PTC patients was significantly upregulated.…”
Section: Exosome Biomarkers For Tcmentioning
confidence: 99%
“…The differentiation between benign and malignant thyroid nodules is still determined by histological examination from the excised thyroid tumor via nodule biopsy or FNAB [ 4 ]. Therefore, a few methods, including specific gene detection by polymerase chain reaction (PCR) technique, have been developed for differentiating from benign and malignant thyroid nodules preoperatively [ 5 ]. According to the World Health Organization (WHO) on the latest classification of thyroid cancer in 2017 [ 6 ], thyroid cancer is mainly classified into papillary thyroid carcinoma (PTC), follicular thyroid carcinoma (FTC), Hürthle (oncocytic) cell carcinoma (HCC), medullary thyroid carcinoma (MTC), poorly differentiated thyroid carcinoma (PDTC), and anaplastic thyroid carcinoma based on their histopathological characteristics [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…CTCs are classified into epithelial type, mesenchymal CTC (MCTC) type, and both mixed types according to their surface markers [ 23 ]. So far, CTC evaluation for thyroid cancer mostly has only a few available data, and the results revealed a little correlation with CTC number [ 5 , 23 , 24 ]. Here, as in the previous description, PTC and FTC have good 5-year OS.…”
Section: Introductionmentioning
confidence: 99%